2018
DOI: 10.1016/j.jcz.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A new cryptic species of Asteronyx Müller and Troschel, 1842 (Echinodermata: Ophiuroidea), based on molecular phylogeny and morphology, from off Pacific Coast of Japan

Abstract: The first phylogenetic and phylogeographic studies of the cosmopolitan deep-sea species, Asteronyx loveni Müller and Troschel, 1842, were conducted, based on specimens collected from off the Pacific coast of Japan. Partial sequences of mitochondrial 16S (68 specimens) and COI ( 24specimens) genes were analyzed. Phylogenetic trees and network analyses revealed three lineages and five sub-lineages of A. loveni. Genetic distance and AMOVA (analysis of molecular variance)analyses suggested that the lineages should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The molecular phylogenetic trees of these species of Gorgonocephalidae and Euryalidae were in agreement with previous studies ( Okanishi and Fujita 2013 ; Christodoulou et al 2019 ; O’Hara et al 2019 ). Previous molecular studies indicated that intraspecific genetic distance ranges approximately from 0.5% to 6.4%, with a mean of 2.2%, but species from the family Euryalidae usually showed less than 2% mean genetic distance ( Okanishi et al 2011 , 2018 ; Okanishi and Fujita 2013 ; Boissin et al 2017 ). In this study, we focused on the genera Asteroschema , Asterostegus , and Astrodendrum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular phylogenetic trees of these species of Gorgonocephalidae and Euryalidae were in agreement with previous studies ( Okanishi and Fujita 2013 ; Christodoulou et al 2019 ; O’Hara et al 2019 ). Previous molecular studies indicated that intraspecific genetic distance ranges approximately from 0.5% to 6.4%, with a mean of 2.2%, but species from the family Euryalidae usually showed less than 2% mean genetic distance ( Okanishi et al 2011 , 2018 ; Okanishi and Fujita 2013 ; Boissin et al 2017 ). In this study, we focused on the genera Asteroschema , Asterostegus , and Astrodendrum .…”
Section: Discussionmentioning
confidence: 99%
“…Two new species are described and seven species are redescribed, including seven new records from the South China Sea and one new record from the Northwest Pacific, all richly illustrated. DNA barcoding was used to identify ophiuroid species in the past two decades ( Ward et al 2008 ; Hoareau and Boissin 2010 ; Okanishi et al 2011 , 2018 ; Okanishi and Fujita 2013 ). Hence, we use barcoding to test our morphological identifications and to understand the interrelationships within genera.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there are the cases when the term ‘cryptic’ species was applied to externally diagnosable species (e.g. in the echinoderm ophiuroids 13 ). Thus, a considerable amount of non-cryptic diversity is still currently included under the ‘cryptic species’ concept.…”
Section: Discussionmentioning
confidence: 99%
“…However, to define an exact degree of morphological disparity is very difficult, if it is possible at all, so Heethoff 10 further concluded that the current ‘cryptic species’ concept represents either conceptual or terminological chaos. Additional complications arise from the most recent practice in different animal groups such as crustaceans 11 , insects 12 or echinoderms 13 when the term ‘cryptic’ species is used for morphologically diagnosable species.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic reconstruction was performed using the maximum likelihood (ML) analysis in RAxML v. 8.1.20 (Stamatakis 2014), and 1,000 bootstraps were used to estimate the node reliability as bootstrap support values. Bootstrap values lower than 75% for each node were considered as insignificant (Okanishi et al 2018). Pontodriluslongissimus was used as the outgroup (Accession number MK642683 and MK642684).…”
Section: Methodsmentioning
confidence: 99%